Blood Pressure Components and the Risk for End-Stage Renal Disease and Death in Chronic Kidney Disease - Agarwal, Rajiv (American Society of Nephrology, 2009)
Background and objectives: Mean arterial pressure has been used in clinical trials in nephrology to randomly assign and treat patients, yet the pulsatile component of BP is recognized to influence outcomes in older people. I examined the unique contributions of systolic (SBP) and diastolic BP (DBP) on the risk for ESRD and death in patients with chronic kidney disease (CKD). Design, setting, participants, & measurements: A single-center, prospective cohort study was conducted of 218 veterans with CKD (22% black, 4% women, mean age 68 yr, clinic BP 154.1 ± 25.1/85.2 ± 13.9 mmHg, 48% with diabetes). Results: During follow-up of up to 7 yr, 63 patients had ESRD and 102 patients died. Compared with those with controlled SBP (<130 mmHg), patients with moderate control (130 to 149 mmHg) had hazard ratio of 3.87 and those with poor control hazard ratio of 9.09 for ESRD. DBP had no direct ability to predict ESRD. For all-cause mortality, a J-shaped relationship was seen for SBP and an inverse relationship was seen for DBP. Considered jointly in the Cox model, a higher SBP and lower DBP improved the prediction of all-cause mortality compared with either BP component alone. The presence of J curve was especially pronounced in patients with advanced CKD, absence of clinical proteinuria, or age >65 yr. Conclusions: In older patients with CKD, SBP predicts ESRD and a higher SBP and lower DBP predicts all-cause mortality. Lower BP of <110/70 mmHg is a marker of higher mortality in older individuals with advanced CKD.